Existence of solutions and controllability of nonlinear integrodifferential systems in Banach spaces - Balachandran K. (Mathematical Problems in Engineering, 2003)
We prove the existence of mild and strong solutions of integrodifferential equations with nonlocal conditions in Banach spaces. Further sufficient conditions for the controllability of integrodifferential systems are established. The results are obtained by using the Schauder fixed-point theorem. Examples are provided to illustrate the theory.